2008
DOI: 10.1104/pp.108.116905
|View full text |Cite
|
Sign up to set email alerts
|

A Proteomic Profiling Approach to Reveal a Novel Role of Brassica napus Drought 22 kD/Water-Soluble Chlorophyll-Binding Protein in Young Leaves during Nitrogen Remobilization Induced by Stressful Conditions

Abstract: Despite its water-soluble chlorophyll-binding protein (WSCP) function, the putative trypsin inhibitor (TI) activity of the Brassica napus drought 22 kD (BnD22) protein and its physiological function in young leaves during leaf nitrogen (N) remobilization promoted by stressful conditions remains an enigma. Therefore, our objectives were to determine (1) if BnD22 is related to the 19-kD TI previously detected in B. napus young leaves, and (2) if the levels of BnD22 transcripts, BnD22 protein, and TI activity in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(57 citation statements)
references
References 79 publications
4
52
1
Order By: Relevance
“…We failed to detect such an activity in vitro with recombinant pigmented BoWSCP or its apoprotein form, in agreement with other reports where WSCP did not significantly inhibit endogenous leaf proteases or other Ser proteases tested (Ilami et al 1997;Nishio and Satoh 1997). However, Desclos et al (2008) reported on a trypsin inhibitor activity of Bnd22, a WSCP accumulated in young leaves of B. napus upon nitrogen (N) starvation or plant treatment with the stress hormone methyl jasmonate. They postulate that during N starvation this WSCP performs two functions, first as a Chl scavenger to protect tissue with degraded Chl-protein complexes from damage by photooxidation, and second as a trypsin inhibitor to delay senescence of young leaves as older leaves undergo senescence for N mobilization.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…We failed to detect such an activity in vitro with recombinant pigmented BoWSCP or its apoprotein form, in agreement with other reports where WSCP did not significantly inhibit endogenous leaf proteases or other Ser proteases tested (Ilami et al 1997;Nishio and Satoh 1997). However, Desclos et al (2008) reported on a trypsin inhibitor activity of Bnd22, a WSCP accumulated in young leaves of B. napus upon nitrogen (N) starvation or plant treatment with the stress hormone methyl jasmonate. They postulate that during N starvation this WSCP performs two functions, first as a Chl scavenger to protect tissue with degraded Chl-protein complexes from damage by photooxidation, and second as a trypsin inhibitor to delay senescence of young leaves as older leaves undergo senescence for N mobilization.…”
Section: Discussionsupporting
confidence: 84%
“…Since the WSCP consensus sequence contains an N-proximal section that is similar to Künitz protease inhibitors, the hypothesis has repeatedly been put forward that WSCP is a stress-induced protease inhibitor. However, an inhibitor activity toward trypsin has only been found in the WSCP-related protein BnD22 from B. napus (Desclos et al 2008), and inhibition of the cysteine protease papain has been demonstrated with a recombinant version of the Arabidopsis thaliana WSCP precursor (Halls et al 2006), whereas no significant protease inhibitor properties were found in other cases (Kamimura et al 1997;Nishio and Satoh 1997).…”
Section: Introductionmentioning
confidence: 99%
“…5). In previous studies, a decrease in leaf N during the growth period has been observed to accompany a decrease in photosynthesis (Pury and Farquhar, 1997) associated with a decrease in leaf chlorophyll content (Desclos et al, 2008). The onset of fructescence in September also coincided, in our study, with an increase in leaf N. This finding may be a result of a reduced demand for N during seed maturation.…”
Section: Relationship Of Leaf N To P Max In Different Phenophasessupporting
confidence: 54%
“…The biochemical markers for the identification of leaf senescence used in this study have already been described in the literature (Masclaux et al, 2000;Desclos et al, 2008). The decreases in chlorophyll and starch content (Fig.…”
Section: Discussion Senescence Induced Changes At the Cell Levelmentioning
confidence: 99%
“…In Arabidopsis (Arabidopsis thaliana) and oilseed rape, N can be remobilized from old to expanding leaves at the vegetative stage during sequential senescence as well as from leaves to seeds at the reproductive stage during monocarpic senescence (Malagoli et al, 2005;Diaz et al, 2008; Lemaitre et al, 2008). Senescence can also be induced by environmental stress such as N starvation (Etienne et al, 2007) or water deficit (Reviron et al, 1992) and propagated from old to mature leaves and delayed in young leaves, suggesting finely tuned high regulation of metabolism at the whole-plant level with consequences for NUE (Desclos et al, 2008). One major challenge to understanding the efficiency of senescenceinduced organic resource reallocation and to highlighting major molecular and mechanistic attributes of nutrient recycling is monitoring the kinetics of the structural reorganization of cell structures.…”
mentioning
confidence: 99%